Motion under gravity: a creative lesson from the paradigm of constructivism / Beh Kian Lim. - Beh, Kian Lim (Universiti Teknologi MARA Cawangan Selangor, 2011)
This paper offers insight into the author’s experience of teaching the topic of motion under gravity to students enrolled in a pre-service science teacher preparation program. The instructional method is based on the activity of the alternative to Galileo’s experiment using the three stage teaching sequences proposed by Nussbaum and Novick from the paradigm of constructivism. The activity reveals the general misconception among pre-service physics teachers and non-physics majors regarding motion under gravity. The paper also highlights the research findings of two studies based on the same classroom activity - the alternative to Galileo’s experiment. The studies involve two groups of Form Four secondary school students from urban and rural settings. The empirical data derived from the study of school students is consistent with the observation data gathered from the pre-service science classroom activity. It is concluded that the usual way of teaching the topic of motion under gravity with the goal of introducing the idea of gravitational acceleration is ineffective To rectify this shortcoming, the author suggests the ‘teach less-learn more’ philosophy that is in line with suggestions made in most recent science education reform documents. It is suggested that insights from this study can contribute to improvements in the training of future science teachers.